2013
DOI: 10.1002/cphc.201201022
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Nuclear Dynamics in the Ammonia Cation: Relation between High‐Harmonic and Photoelectron Spectroscopies

Abstract: We report measurements of the umbrella motion in the ammonia cation on the attosecond time scale. The motion is prepared by strong‐field ionization and probed by photorecombination through the process of high‐harmonic generation. Performing such measurements at multiple wavelengths (0.8, 1.44, 1.8 μm) enables us to follow the nuclear dynamics over a broad temporal range (0.8–3.8 fs). The intensity of the driving field is found to have a significant impact on the observed dynamics through the vibrational‐state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
3
39
0
2
Order By: Relevance
“…more than 73 % of the molecules pointing in the same direction, under completely field-free conditions. Details of the experimental setup have been given elsewhere [26,34]. The degrees of orientation obtained in this study rival those obtained after quantum-state selection [23] with a ∼10 6 -fold increase in particle density.…”
supporting
confidence: 63%
“…more than 73 % of the molecules pointing in the same direction, under completely field-free conditions. Details of the experimental setup have been given elsewhere [26,34]. The degrees of orientation obtained in this study rival those obtained after quantum-state selection [23] with a ∼10 6 -fold increase in particle density.…”
supporting
confidence: 63%
“…Nuclear motion of HCCI + following strong-field ionization was included through the approach outline in Ref. 105, i.e., through nuclear auto-correlation functions 46,106 derived from experimental photoelectron spectra 107 . Finally, since the molecules were not perfectly aligned, the variation of the strong-field-ionization rate with the alignment angle was also required.…”
Section: Charge Migrationmentioning
confidence: 99%
“…This orientation has been already experimentally realized and variation of the orientation did not reveal contributions to the ionization from lower lying orbitals [5]. The TDSE ionization yields are compared to the ones obtained using Ammosov-Delone-Krainov (ADK) tunneling rates Γ ADK [14,15] and the recently introduced frequency-corrected ADK (FC-ADK) model [18] based on the Perelomov-Popov-Terent'ev (PPT) [13] theory.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the required nuclear autocorrelation functions can be obtained from photoelectron spectra [4][5][6]. The photoelectron spectra revealed that the inversion (or umbrella) mode is the only vibrational mode in which a significant nuclear motion is triggered by the laser field [5]. Importantly, it was shown that the strong geometrydependence of the ionization rate, the key ingredient for Lochfraß, must indeed be considered in order to quantitatively match the experimental PACER results [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation